Collectivistic Leadership in Context: An Examination of How and When Collective Charismatic Leadership Relates to Unit Functioning. (May 2021) - Ziegert, Jonathan C.; Mayer, David M.; Piccolo, Ronald F.; Graham, Katrina A.
This research explores the nature of collective leadership by examining the boundary conditions of how and when it relates to unit functioning. Building from a contingency perspective that considers the impact of contextual factors, we propose that collective charismatic leadership will be associated with lowered unit conflict, and this relationship will be strengthened by the contingency elements of individual charismatic leadership, task complexity, and social inclusion. Furthermore, we propose that the interactions of collective charismatic leadership with these contextual factors will relate to performance and satisfaction through conflict. We examine our hypotheses across two unit-level field studies, and the results illustrated that high levels of these contextual factors enhanced the negative relationship between collective charismatic leadership and conflict, which generally mediated the relationships between these interactive effects and performance and satisfaction. The results also highlight the detrimental aspects of collective leadership and how it can relate to reduced unit functioning when it is not aligned with an appropriate context. Overall, these findings begin to provide a more complete picture of collective leadership from a contingency perspective through a greater understanding of when and how it is related to unit functioning.